Introduction to robotic design: theory, hardware and programming - Rahman, Md. Mozasser (2017)
Overview of robots. Robot kinematics and dynamics. Control and sensing systems, robot vision. Programming and interfacing. Basics of robot design and robot test. Applications of robots.